2000
DOI: 10.1093/jn/130.11.2697
|View full text |Cite
|
Sign up to set email alerts
|

Daily Iron Supplementation Is More Effective than Twice Weekly Iron Supplementation in Pregnant Women in Pakistan in a Randomized Double-Blind Clinical Trial

Abstract: In the context of limited effectiveness of iron supplementation programs, intermittent iron supplementation is currently under debate as a possible alternative strategy that may enhance the effectiveness of operational programs. This field-based trial assessed the outcome of twice weekly iron supplementation compared to daily in Pakistan. A double-blind, randomized, clinical trial was conducted in Northern Pakistan. Anemic pregnant women (n = 191) were assigned to receive daily (200 mg ferrous sulfate) or twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 24 publications
4
40
0
4
Order By: Relevance
“…Both groups had similar rates of anaemia at delivery, providing evidence that low doses of iron during pregnancy could be beneficial in preventing anaemia. A number of studies showed that reducing the iron dose or intermittent prescriptions are less effective in improving Hb and iron status than a daily standard dose (30-60 mg elemental iron) [1,8,12]. However, this difference was small, with no reported significant effect on pregnancy outcomes and might be related to factors other than type of iron regimen, such as pre-pregnancy haematological status, nutritional behaviour, diet during pregnancy and the prevalence of iron deficiency or other micronutrient deficiencies [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both groups had similar rates of anaemia at delivery, providing evidence that low doses of iron during pregnancy could be beneficial in preventing anaemia. A number of studies showed that reducing the iron dose or intermittent prescriptions are less effective in improving Hb and iron status than a daily standard dose (30-60 mg elemental iron) [1,8,12]. However, this difference was small, with no reported significant effect on pregnancy outcomes and might be related to factors other than type of iron regimen, such as pre-pregnancy haematological status, nutritional behaviour, diet during pregnancy and the prevalence of iron deficiency or other micronutrient deficiencies [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread preventive programmes, iron-deficiency anaemia during pregnancy is still prevalent and is associated with adverse pregnancy outcomes for both mother and newborn [1][2][3][4]. Poor client compliance with national iron supplementation protocols because of side-effects, especially gastrointestinal (GI) complications such as nausea, vomiting and constipation, is suggested as one of the main reasons for the inefficiency of these programmes [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention and control is typically achieved through iron fortification of food staples like flour, rice, and pasta, and/or through administration of iron supplements most often in iron pill or, more recently sprinkle form (Baltussen et al, 2004;Faqih et al, 2006;Mumtaz et al 2000;. Although iron supplements are widely available and fortified foods constitute a major component of the diet in the developed world, access is limited in the developing world and cost if often prohibitive.…”
Section: Introductionmentioning
confidence: 99%